2018
DOI: 10.1136/jmedgenet-2018-105319
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new risk factors for rolandic epilepsy: CNV at Xp22.31 and alterations at cholinergic synapses

Abstract: BackgroundRolandic epilepsy (RE) is the most common genetic childhood epilepsy, consisting of focal, nocturnal seizures and frequent neurodevelopmental impairments in speech, language, literacy and attention. A complex genetic aetiology is presumed in most, with monogenic mutations in GRIN2A accounting for >5% of cases.ObjectiveTo identify rare, causal CNV in patients with RE.MethodsWe used high-density SNP arrays to analyse the presence of rare CNVs in 186 patients with RE from the UK, the USA, Sardinia, Arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…However, equally there is no reason to believe that GPs would systematically not be more specific in coding having received confirmation of a specific epilepsy syndrome from hospital specialists. Given identification of copy number variants at Xp22.31 as a risk factor for RE, we hypothesise higher incidence in males may be related to an X linked recessive genetic pre-disposition 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, equally there is no reason to believe that GPs would systematically not be more specific in coding having received confirmation of a specific epilepsy syndrome from hospital specialists. Given identification of copy number variants at Xp22.31 as a risk factor for RE, we hypothesise higher incidence in males may be related to an X linked recessive genetic pre-disposition 4…”
Section: Discussionmentioning
confidence: 99%
“…Information on frequency, cause and natural history of Rolandic epilepsy (RE) is necessary to develop optimal treatment strategies. There are few published studies on the incidence of RE 1–4…”
Section: Introductionmentioning
confidence: 99%
“…In patients with epilepsy, Olson et al [5] found at least one copy number variant on chromosomal microarray in 323 out of 805 studied cases (40%), and 30 of these (9.3%) had Xp22.31 microduplication. Recently, Addis et al [6] found this duplication in 2.2% of patients with benign childhood epilepsy with centrotemporal spikes (BECTS). Even if the clinical significance of the rearrangement is still debated, the most recent studies confirm its possible pathogenic role, although probably not independently but instead linked to additional genetic factors [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Epileptic encephalopathy (EE) is a group of brain disorders often with childhood onset and 53 accompanied by serious neurocognitive consequences (Jain et al, 2013). While linkage and 54 association studies have suggested that ARFGEF1 is involved in genetic epilepsy (Wallace et 55 al., 1996;Piro et al, 2011;Addis et al, 2018), it was one of several candidate genes and no 56 specific causal ARFGEF1 variants were indicted previously. 57 58 ARFGEF1 encodes Brefeldin A (BFA) inhibited guanine-nucleotide-exchange protein-1, also 59 known as BIG1 (Addis et al, 2018); and is highly conserved across mammals and eukaryotes 60 (Wright et al, 2014).…”
Section: Introduction 52mentioning
confidence: 99%
“…For 334 example, in a large Australian family spanning three generations in which CRH had been 335 proposed as a EE candidate gene (Wallace et al, 1996), Piro and colleagues later suggested 336 that ARFGEF1 was also plausible (Piro et al, 2011). In another study of copy number variants 337 (CNV), the authors reported an EE patient with onset of 10 years with ARFGEF1 and CSPP1 338 as candidate genes (Addis et al, 2018). In our study, the Lennox-Gastaut patient also carried a 339 nonsynonymous BMP2 variant; while BMP2 is not yet associated with epilepsy at least one 340 study has shown that BMP2 signaling promotes the differentiation of some GABAergic 341 neurons (Yao et al, 2010).…”
mentioning
confidence: 99%